Peningkatan Kemampuan Pemahaman Matematis dan Motivasi Belajar Matematika Siswa Melalui Penerapan Model Discovery Learning Berbantuan Macromedia Flash 8 - Ulfa Nuriza; Saminan Saminan; Zainal Abidin (Universitas Syiah Kuala, 2019)
The purpose of mathematics learning in Permendikbud No. 59 of 2014 requires students are able to understand mathematical concepts, explain the link between concepts and apply concepts or algorithms, are flexible, accurate, efficient, and precise in troubleshooting. But the facts show the students have not been able to understand mathematical concepts well. This condition can be caused by many factors, including students' motivation in learning, models and media used by teachers during the learning process. One model of learning that is presumed to help students to improve understanding and motivation is model of discovery learning aided Macromedia Flash 8. The purpose of this study to determine the increase of understanding mathematical ability and motivation taught with discovery learning aided Macromedia Flash 8 as well as the correlations between mathematical understanding ability and motivation to learn mathematics. This study was an experimental study with pretest-posttest study design group design. The population throughout class XI student of Madrasah Aliyah Negeri 1 Sigli, random sample selection is done to determine the experimental class (XI IPA3) and the control class (XI IPA6). The instrument used in this study consisted of mathematical understanding ability instrument and motivation questionnaire of study mathematics. Based on the results of data analysis using t-test and test of product moment correlation of Pearson gained increased mathematical understanding ability and motivation to learn math through discovery learning model aided Macromedia Flash 8 is better than applying the model of discovery learning but not significant, there is a relationship between the ability of mathematical understanding and motivation through discovery learning model aided macromedia flash 8, the degree of closeness relationship is in enough category.